Vibration reduction of monopile-supported offshore wind turbines based on finite element structural analysis and active control. (1st November 2022) - Alkhoury, Philip; Aït-Ahmed, Mourad; Soubra, Abdul-Hamid; Rey, Valentine
Abstract: A finite element (FE) structural analysis based on a commercial software is combined with an observer-based active control to study the real-time performance of an Active Tuned Mass Damper (ATMD) in reducing the fore-aft vibration of a monopile-supported offshore wind turbine (OWT). Firstly, a reduced order MDOF model was established and used to design a Linear Quadratic Regulator. Secondly, the controller was combined with an observer to minimize the required number of sensors. Thirdly, co-simulations between the high-fidelity FE software and the optimized controller were performed. The aim was to test the robustness of the MDOF model-based controller in terms of OWT vibration reduction when the ATMD is used within a structural FE commercial software. The optimized controller applied to the FE mechanical model of the OWT proved to be efficient, the RMS reduction ratio of the tower top displacement being around 60%. Given the increasing size and capacity of OWTs, the proposed co-simulation technique combining a large deformation structural analysis based on a FE commercial software with an optimized observer-based active control can serve as a tool for the final design stage of the next-generation dynamically-sensitive OWT structures to accurately capture their dynamic responses in the presence of ATMDs. Highlights: Co-simulation combining FE structural analysis with an active control was used to simulate the vibration reduction of an OWT. The active control was performed through the implementation of an optimal LQR controller combined with a LQ state observer. The co-simulation technique can serve as a tool for the final design stage of the next-generation dynamically-sensitive OWTs.